2020
DOI: 10.3390/ijms21207485
|View full text |Cite
|
Sign up to set email alerts
|

Diabetes Mellitus-Related Dysfunction of the Motor System

Abstract: Although motor deficits in humans with diabetic neuropathy have been extensively researched, its effect on the motor system is thought to be lesser than that on the sensory system. Therefore, motor deficits are considered to be only due to sensory and muscle impairment. However, recent clinical and experimental studies have revealed that the brain and spinal cord, which are involved in the motor control of voluntary movement, are also affected by diabetes. This review focuses on the most important systems for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
31
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 42 publications
(33 citation statements)
references
References 219 publications
1
31
0
1
Order By: Relevance
“…As such, much of the diabetic body of literature focuses on sensory neuropathy as this is the primary clinical concern, but the contributive impact of AGEs in diabetic neuropathogenesis needs further study. It has been posited that motor neurons are partially protected by the central nervous system blood–brain barrier from the glycolytic attack that sensory nerve cell bodies experience in the diabetic state [ 140 , 141 ]. Additionally, other compensatory mechanisms likely exist for motor nerves (e.g., single motor unit action potential enlargement) that sensory nerves lack [ 142 ].…”
Section: Peripheral Nerve Involvement In Aging and Atrophymentioning
confidence: 99%
“…As such, much of the diabetic body of literature focuses on sensory neuropathy as this is the primary clinical concern, but the contributive impact of AGEs in diabetic neuropathogenesis needs further study. It has been posited that motor neurons are partially protected by the central nervous system blood–brain barrier from the glycolytic attack that sensory nerve cell bodies experience in the diabetic state [ 140 , 141 ]. Additionally, other compensatory mechanisms likely exist for motor nerves (e.g., single motor unit action potential enlargement) that sensory nerves lack [ 142 ].…”
Section: Peripheral Nerve Involvement In Aging and Atrophymentioning
confidence: 99%
“…T1DM causes insulin deficiency with effects on the expression of neurotrophic factors, neurotransmission, loss of functional integrity, and defects in brain connectivity. T2DM causes cognitive decline and dementia due to decreased insulin sensitivity [111][112].…”
Section: Cyclo-oxygenase Pathwaymentioning
confidence: 99%
“…Imaging shows a decreased volume of the hippocampus and electrophysiological studies reveal a reduction in long-term potentiation. This causes a decline in learning, memory, and affective expression [112,114].…”
Section: Cyclo-oxygenase Pathwaymentioning
confidence: 99%
See 1 more Smart Citation
“…These motor dysfunctions were previously believed to be caused by a combination of sensory neuropathy and muscle wasting [ 5 ]. However, recent studies have revealed that motor system dysfunction, including the cerebral cortex and spinal cord, can also cause motor dysfunction in these patients [ 6 , 7 ].…”
Section: Introductionmentioning
confidence: 99%